An in situ time-resolved neutron diffraction study of the hydrothermal crystallisation of barium titanate - Walton, R; Smith, R; Millange, F; Clark, I; Sinclair, D; O'Hare, D (2000)
The hydrothermal crystallisation of barium titanate, BaTiO3, has been studied for the first time by in situ time-resolved neutron powder diffraction; we deduce that BaTiO3 is formed from solution by reaction between [Ti-(OH)(x)]((4-x))+((aq)) and [Ba(OH)(x)]((2-x))+((aq)) species, rather than by a heterogeneous reaction between solid TiO2 and Ba2+((aq)) ions.